2007
DOI: 10.1080/00016340701625347
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and urinary incontinence – prevalence data from Norway

Abstract: We found a strong association between diabetes and urinary incontinence, especially for urge incontinence and severe degree of incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
62
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 23 publications
11
62
5
2
Order By: Relevance
“…8,10,14,30 In our study, SUI affected 15.9% of climacteric women and was similar to the population findings by Brito et al 8 With regard to factors associated with UI, the literature is controversial and often shows association between UI and socio-demographic data such as age, education and race; obstetric factors such as pregnancy, multiparity, type of delivery, newborn weight; gynecological factors such as gynecological surgeries and menopausal status; and morbidities such as diabetes mellitus and obesity. 1,4,[27][28][29][30][31] The bivariate analysis performed in our study showed a positive association with education, skin color, pregnancy, gynecologic surgery, which was not confirmed in the logistic regression. Our findings are in line with those documented by Brito et al 8 and Guarisi et al, 14 who also found no association between UI and socioeconomic and reproductive factors.…”
Section: Discussionmentioning
confidence: 92%
“…8,10,14,30 In our study, SUI affected 15.9% of climacteric women and was similar to the population findings by Brito et al 8 With regard to factors associated with UI, the literature is controversial and often shows association between UI and socio-demographic data such as age, education and race; obstetric factors such as pregnancy, multiparity, type of delivery, newborn weight; gynecological factors such as gynecological surgeries and menopausal status; and morbidities such as diabetes mellitus and obesity. 1,4,[27][28][29][30][31] The bivariate analysis performed in our study showed a positive association with education, skin color, pregnancy, gynecologic surgery, which was not confirmed in the logistic regression. Our findings are in line with those documented by Brito et al 8 and Guarisi et al, 14 who also found no association between UI and socioeconomic and reproductive factors.…”
Section: Discussionmentioning
confidence: 92%
“…In several US studies, stress urinary incontinence is more common in white women than in African-American or Asian-American women 19,34,35 . Other factors associated with urinary incontinence in multiple, large, population-based studies 25,[36][37][38] include parity 25,26,36 , obesity 25,26,36,38 , …”
mentioning
confidence: 99%
“…Diabetes has been implicated in fall risk (Volpato et al 2005), fractures (Schwartz et al 2001), urinary incontinence (Ebbesen et al 2007) and depression (Anderson et al 2001). …”
Section: Diabetes and Geriatric Syndromesmentioning
confidence: 99%